2021
DOI: 10.7717/peerj.10602
|View full text |Cite
|
Sign up to set email alerts
|

Effects of oxygen exposure on relative nucleic acid content and membrane integrity in the human gut microbiota

Abstract: While the diversity of the human gut microbiota is becoming increasingly well characterized, bacterial physiology is still a critical missing link in understanding how the gut microbiota may be implicated in disease. The current best practice for studying bacterial physiology involves the immediate storage of fecal samples in an anaerobic chamber. This reliance on immediate access to anaerobic chambers greatly limits the scope of sample populations that can be studied. Here, we assess the effects of short-term… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 45 publications
1
2
0
Order By: Relevance
“…Overall, our study indicated no influence between aerobic and anaerobic sample transport materials during sample collection and sample transport (provided that the metagenomic extraction was performed within 2 days) on fecal microbiota and fecal quantitative microbiota. Our results were consistent with Taguer, Quillier & Maurice (2021) that short period of oxygen exposure did not affect the nucleic acid content and changes of bacterial microbiota. Moreover, studies reported that the fecal samples for microbiome studies might be kept without any DNA stabilizer reagent at 4 °C for up to 8 weeks and at −20 °C for the longer period ( Choo, Leong & Rogers, 2015 ; Song et al, 2016 ).…”
Section: Discussionsupporting
confidence: 93%
“…Overall, our study indicated no influence between aerobic and anaerobic sample transport materials during sample collection and sample transport (provided that the metagenomic extraction was performed within 2 days) on fecal microbiota and fecal quantitative microbiota. Our results were consistent with Taguer, Quillier & Maurice (2021) that short period of oxygen exposure did not affect the nucleic acid content and changes of bacterial microbiota. Moreover, studies reported that the fecal samples for microbiome studies might be kept without any DNA stabilizer reagent at 4 °C for up to 8 weeks and at −20 °C for the longer period ( Choo, Leong & Rogers, 2015 ; Song et al, 2016 ).…”
Section: Discussionsupporting
confidence: 93%
“…Due to its nonintrusive nature, human stool sampling is a powerful surrogate for the gut microbiota, as bacteria can remain metabolically active when rapidly placed in anoxic conditions 35 , 73 , 74 . However, it should be recognized that stool samples do not provide information on the location of specific gut bacteria along the digestive tract or across the depth of the mucus layer and that its composition represents shed bacteria 75 .…”
Section: Discussionmentioning
confidence: 99%
“…For instance, the gut microbiome affects the activity of enzymes involved in the metabolism of TCM compounds, such as cytochrome P450 enzymes ( Boer et al., 2016 ; Tang et al., 2022 ). Also, intestinal flora alters the expression of transporters that are responsible for moving TCM compounds across cell membranes, which can affect their absorption and bioavailability ( Taguer et al., 2021 ; Togao et al., 2021 ). Furthermore, the gut microbiome produces metabolites that interacts with TCM compounds, potentially affecting their efficacy and safety ( Chen et al., 2021 ; Yang and Wu, 2023 ).…”
Section: Introductionmentioning
confidence: 99%